Optimization Strategies for Industrial Heritage Landscape Design in Zhengzhou - Lu, Hongyu; Nasir, Nadia Binti Mohd (Journal of Literature and Arts Research, 2025)
As Zhengzhou, a key industrial and transportation hub in central China, urbanizes, its industrial heritage becomes a key space where historical culture and modern functions intersect. The challenge in urban renewal is preserving historical value while adapting to modern needs. This paper analyzes Zhengzhou's industrial heritage renovation cases, focusing on the integration of historical preservation, green design, and social function innovation. It identifies issues such as conflicts between preservation and modern demands, insufficient ecological restoration, and the lack of social functions. The paper proposes strategies, including multi-level cultural expression, integrating green design with ecological restoration, and social function innovation, to ensure sustainable development. This research provides both theoretical support and practical guidance for Zhengzhou's transformation and offers insights for other cities with similar challenges.